El Comandante Victor Dreke: The Making of a Cuban Revolutionary. Issue 4 (2nd October 2019) - Brock, Lisa
Abstract : Victor Emilo Dreke Cruz is a walking archive. Today, at age 82, his life represents the arch of the Cuban Revolution. He was fifteen in 1952, when General Batista waged a military coup in order to protect US neo-colonial and Cuban elite interests. It was at this moment that Dreke joined the resistance. First as an organizer, then in charge of a sabotage unit, and then as leader of campaigns against the dictator's police and army. Once the revolution succeeded he took leadership in the Revolutionary Armed Forces. He battled US supported counter-revolutionary forces at the Bay of Pigs and in the Escambray Mountains and joined Che Guevara in the Congo after the assassination of Patrice Lumumba. He worked with the brilliant theorist Amilcar Cabral in Guinea Bissau and Cape Verde, and trained numerous leaders from Africa in Cuba. This article examines the extraordinary life of this man in the context of extraordinary events.